Edukasi Manajemen Penurunan Fleksibilitas pada Lansia di Desa Kwagean - Eka Syahrul Afrian; Tsamara Bunga Maulida; Khoirunnisa; Karima; Hana Salsabila; Sigit Adi Setiawan; Kurnia Al Fandi; M Wildan Purnama; Nuniek Nizmah Fajriyah; Slamet (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Aging is a natural process experienced by every individual and is often accompanied by various physiological changes. One of the most noticeable changes is the decline in muscle and joint flexibility among the elderly. This condition can lead to limited mobility, reduced functional ability, and difficulties in performing daily activities such as walking, bending, or doing simple household chores. Decreased flexibility is also associated with an increased risk of falls and injuries, making it an important issue in maintaining the quality of life of older adults. This study aimed to examine the effect of flexibility management education on the elderly in Kwagean Village. The research design used was pre-experimental with a one-group pre-test post-test approach. A total of 20 elderly participants were selected purposively and attended the educational program, which was conducted after regular elderly exercise sessions. The education was delivered through lectures, discussions, and demonstrations of simple exercises that can be practiced at home to maintain muscle and joint flexibility. Data were collected using a knowledge questionnaire about flexibility and the sit-and-reach test as a measure of physical ability. The results showed an increase in the average knowledge score from 65.0 in the pre-test to 85.0 in the post-test. In addition, there was an improvement in the average flexibility score from 15.2 cm to 20.8 cm after the intervention. Statistical analysis indicated a significant difference (p<0.05), meaning that flexibility management education was proven effective. These findings suggest that education combined with physical activity can positively impact both knowledge and physical ability in the elderly. Practically, such programs can be implemented regularly at the village or community health post level to prevent functional decline. Thus, flexibility management education serves as a promotive and preventive strategy to improve the quality of life and independence of older adults in carrying out daily activities.